PENGARUH PEMBELAJARAN BERBASIS KERJA TERHADAP WAWASAN WIRAUSAHA - Muhammad Yahya (Jurnal Kependidikan, 2016)
THE EFFECT OF WORK-BASED LEARNING ON ENTREPRENEURIAL INSIGHTS Abstract:This study aims to determine the effect of work-based learning on entrepreneurial insights. This research uses Ex-post Facto with correlational approach. Subject of this research are 315 students grade 2 and 3 of Junior High School (Sekolah Menengah Pertama, SMP). Research instrument used questionnaire and documentation. The instruments were validated by using confirmatory factor analysis. Then, Structural Equation Modeling (SEM) were used to analyze the effect of work-based learning on students’ entrepreneurial insight. The results show: (1) model of work-based learning can significantly develop students’ entrepreneurial insights, (2) variable in term of working guidance can build students' entrepreneurial insights significantly with a contribution of 1.96%, (3) variable about work interest can build students 'entrepreneurial insights significantly with a contribution of 6.25%, (4) technological mastery variables can develop students' entrepreneurial insights significantly with a contribution of 5.29%, (5) working appreciation variables can build students 'entrepreneurial insights significantly with a contribution of 12.96%, and (6) variable learning satisfaction can build students' entrepreneurial insights significantly with a contribution of 49%. Keywords:  work-based learning, work guidance, work interest, technology mastery,  learning satisfaction, entrepreneurial insight.